Analisis Faktor-Faktor yang Mempengaruhi Kepatuhan Wajib Pajak Orang Pribadi Pasca Pandemi Covid-19 di Kota Yogyakarta - Masrohah, Siti; Segarawasesa, Fajar Satriya (CV. Ulil Albab Corp, 2024)
Indonesia is a developing country. Therefore, Indonesia requires a substantial amount of state income revenue to support national development financing in all domains, including economic, social, cultural, and legal development. The purpose of this study is to examine the impact of tax amnesty, taxpayer awareness, e-SPT, e-filing, and service quality on individual taxpayer compliance in Yogyakarta. This research technique employed a quantitative approach based on a test of multiple linear regression analysis. The research data were questionnaire-collected primary data. The population of this survey consisted of 64,323 individual taxpayers registered at KPP Pratama Yogyakarta. This study's sample size was 100 respondents, and the method used to select this sample was accidental sampling. This study's findings indicate that tax amnesty has no impact on individual taxpayer compliance, taxpayer awareness has a positive impact on individual taxpayer compliance, the e-SPT system has no impact on individual taxpayer compliance, the e-filing system has no impact on individual taxpayer compliance, and service quality has no impact on individual taxpayer compliance.